2006
DOI: 10.1088/0964-1726/15/5/020
|View full text |Cite
|
Sign up to set email alerts
|

Identification of structural damage using multifunctional Bragg grating sensors: I. Theory and implementation

Abstract: Structural health monitoring has become a respected and established discipline in engineering. Health monitoring involves the development of autonomous systems for continuous monitoring, inspection and damage detection of structures with minimum involvement of labour. The ultimate goal of structural health monitoring is to increase reliability, improve safety, enable light-weight design and reduce maintenance costs for all kinds of structures. The identification of structural damage is therefore a key issue in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 15 publications
2
50
0
Order By: Relevance
“…compared to Fiber Bragg Gratings (FBG), is the possibility to be tailored for the specific application. Focusing on high frequency dynamics, several works related to FBG acquisition have shown that a key parameter affecting the grating response is the ratio between the ultrasonic wavelength and the grating length [15][16][17]. The same considerations reasonably hold for interferometric sensors, which perform a spatial integration over the sensing length of the ultrasonic signals: if an excessive sensing length is chosen, the overall integration may drastically degrade the sensor sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…compared to Fiber Bragg Gratings (FBG), is the possibility to be tailored for the specific application. Focusing on high frequency dynamics, several works related to FBG acquisition have shown that a key parameter affecting the grating response is the ratio between the ultrasonic wavelength and the grating length [15][16][17]. The same considerations reasonably hold for interferometric sensors, which perform a spatial integration over the sensing length of the ultrasonic signals: if an excessive sensing length is chosen, the overall integration may drastically degrade the sensor sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…A similar FBG sensing method was also presented by Betz et al [108], [109], [110]. Their system is intended to monitor and detect Lamb waves, and was implemented in a Perspex plate.…”
Section: Fiber Bragg Grating (Fbg) Sensorsmentioning
confidence: 97%
“…As the acquisition rate of wavelength interrogators increased, the first dynamic study appeared. Betz et al used FBGs for the monitoring and detection of Lamb waves [32][33][34], while other groups investigated the possibility of using FBGs for dynamic strain sensing [35][36][37]. In 2009, Seo et al studied the sensitivity enhancement of FBG sensors for acoustic emission detection [38].…”
Section: Fiber Bragg Gratingsmentioning
confidence: 99%